2020
DOI: 10.3390/admsci10020028
|View full text |Cite
|
Sign up to set email alerts
|

The Circular Economy Business Model: Examining Consumers’ Acceptance of Recycled Goods

Abstract: The circular economy strategy supports the transformation of the linear consumption model into a closed-production model to achieve economic sustainability, with the consumers’ acceptance of circular products being one of the major challenges. Further, one important aspect of product circularity remains unexplored, such as the consumers’ purchase intention of recycled circular goods. In this context, the present study proposes and tests a conceptual model on consumers acceptance of recycled goods through PLS S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 44 publications
2
68
4
Order By: Relevance
“…In recent years, it has been shown that recycled materials are increasingly well accepted by consumers in our countries and throughout the world [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been shown that recycled materials are increasingly well accepted by consumers in our countries and throughout the world [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach also resulted in reduced carbon footprint and chemical processing thereby promoting green procurement and manufacturing. Recent studies also confirm that recycling and reuse of materials in manufacturing results in resource conservation, reduced carbon emissions, cleaner production processes and environmental protection (Mativenga et al , 2017; Oberholzer et al , 2017; Garcés-Ayerbe et al , 2019; Calvo-Porral and Lévy-Mangin, 2020; Kristoffersen et al , 2020).…”
Section: Results and Interpretationmentioning
confidence: 84%
“…Currently there are already academic studies focusing on the development of robots that can make such classification [44], or those that applying deep learning techniques in the automation of the process [45], and even applied to agricultural policy, undoubtedly affecting sustainability [46]. As indicated by [47] "gain environmental, energy, and economic benefits" or [48] "the important role of consumers in circular economy business models through the examination of consumers' acceptance of recycled goods", this system allows automatic and individual recycling; and as shown by the study of [49] this recycling can even help convert waste into energy. A circular economy based on the self-recycling of elements that today are wasted and thrown directly into the garbage can be very positive if combined with other measures in favor of the environment such as incentives for low polluting vehicles [50], new and more sustainable ways of transportation [51], which will undoubtedly result in a better welfare state [52].…”
Section: Discussionmentioning
confidence: 99%